Butyrate Protects Mice from Clostridium difficile-Induced Colitis through an HIF-1-Dependent Mechanism - José Luís Fachi; Jaqueline de Souza Felipe; Laís Passariello Pral; Bruna Karadi da Silva; Renan Oliveira Corrêa; Mirella Cristiny Pereira de Andrade; Denise Morais da Fonseca; Paulo José Basso; Niels Olsen Saraiva Câmara; Éricka Lorenna de Sales e Souza; Flaviano dos Santos Martins; Suzana Eiko Sato Guima; et al. (Cell Reports, 2019)
Summary: Antibiotic-induced dysbiosis is a key factor predisposing intestinal infection by Clostridium difficile. Here, we show that interventions that restore butyrate intestinal levels mitigate clinical and pathological features of C. difficile-induced colitis. Butyrate has no effect on C. difficile colonization or toxin production. However, it attenuates intestinal inflammation and improves intestinal barrier function in infected mice, as shown by reduced intestinal epithelial permeability and bacterial translocation, effects associated with the increased expression of components of intestinal epithelial cell tight junctions. Activation of the transcription factor HIF-1 in intestinal epithelial cells exerts a protective effect in C. difficile-induced colitis, and it is required for butyrate effects. We conclude that butyrate protects intestinal epithelial cells from damage caused by C. difficile toxins via the stabilization of HIF-1, mitigating local inflammatory response and systemic consequences of the infection. : Fachi et al. demonstrate that butyrate is able to protect the intestinal epithelium from the damage caused by Clostridium difficile toxins by stabilizing HIF-1 and increasing tight junctions, which reduces intestinal epithelial permeability, thus inhibiting intestinal inflammation and bacterial translocation. Keywords: short chain fatty acids, microbiota, hypoxia, colitis, intestinal epithelial cells, infection